2012
DOI: 10.1111/j.1420-9101.2012.02519.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Wolbachia protects mosquitoes against Plasmodium‐induced mortality in a natural system

Abstract: In recent years, there has been a shift in the one host‐one parasite paradigm with the realization that, in the field, most hosts are coinfected with multiple parasites. Coinfections are particularly relevant when the host is a vector of diseases, because multiple infections can have drastic consequences for parasite transmission at both the ecological and evolutionary timescales. Wolbachia pipientis is the most common parasitic microorganism in insects, and as such, it is of special interest for understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…Some of these associations produced pathogen interference, however for w AlbB infections of Anopheles gambiae , Plasmodium berghei infection was enhanced [31]. This enhancement may be temperature dependent [32], and has also been observed for some native Wolbachia infections, including in Culex pipiens where Wolbachia protects the host against Plasmodium -induced mortality, but also increases susceptibility to infection [3335]. Interestingly, such enhancement has never been observed for Plasmodium species that infect humans, or in a mosquito with a stable Wolbachia transinfection.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these associations produced pathogen interference, however for w AlbB infections of Anopheles gambiae , Plasmodium berghei infection was enhanced [31]. This enhancement may be temperature dependent [32], and has also been observed for some native Wolbachia infections, including in Culex pipiens where Wolbachia protects the host against Plasmodium -induced mortality, but also increases susceptibility to infection [3335]. Interestingly, such enhancement has never been observed for Plasmodium species that infect humans, or in a mosquito with a stable Wolbachia transinfection.…”
Section: Introductionmentioning
confidence: 99%
“…The type of association within the host is depicted by symbols (target: natural infection, square: stable artificial infection, diamond: transient artificial infection). Numbers indicate: (1) the phenotype is temperature sensitive, (2) Wolbachia infection also increases insect life span [31], which has implications for pathogen transmission. Phylogeny was reconstructed based on work from Carlton et al [26] and Martinsen et al [27].…”
mentioning
confidence: 99%
“…Recent studies carried out in Culex pipiens mosquitoes, which are naturally infected with the w Pip Wolbachia strain and transmit the avian malaria parasite P. relictum , have also demonstrated Plasmodium enhancement. In this natural system, Wolbachia protects the mosquito host against the detrimental fitness effects incurred by Plasmodium infection [31] and increases the susceptibility of C. pipiens to P. relictum , with w Pip-infected mosquitoes having a higher prevalence of Plasmodium sporozoites in the salivary glands [16]. These studies show that the Plasmodium -inhibiting properties of Wolbachia are far from universal; certain mosquito– Wolbachia – Plasmodium combinations and experimental conditions transform Wolbachia -infected mosquitoes into better vectors of malaria parasites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wolbachia are intracellular and endosymbiotic bacteria that infect approximately two-thirds of insect species along with numerous other arthropods. Moreover, they are potent modulators of pathogen infection, and although Anopheles mosquitoes are naturally uninfected with these bacteria, artificial infections have shown that Wolbachia strains reduce the level of P. falciparum, although in contrast, a Wolbachia strain enhances oocyst density of P. berghei , the model murine malaria species [251-253]. Infection with Wolbachia can protect mosquitoes against Plasmodium -induced mortality in a natural system [253].…”
Section: Resultsmentioning
confidence: 99%